2016
DOI: 10.1038/srep27430
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine plays critical role in allergic airway disease manifestation

Abstract: Phospholipase A2 (sPLA2), pivotal for allergic and inflammatory response, hydrolyses phosphatidylcholine (PC) to lysophosphatidylcholine (LPC). In present study, the role of LPC in allergic airway disease manifestation was studied using mouse model. Balb/c mice were immunized using cockroach extract (CE) and LPC release was blocked by sPLA2 inhibitor. Airway hyperresponse (AHR), lung-histology, total and differential leukocyte count (TLC&DLC), Th2 type cytokines, sPLA2 activity and LPC levels in bronchoalveola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 35 publications
(66 reference statements)
3
44
0
Order By: Relevance
“…In this study, we found that lysoglycerophospholipids, such as LPA and LPC, and glycerophospholipid metabolism, including PA, PC, and PI, were significantly altered in plasma from patients with psoriasis (Figs 4 and 6B and C). LPC and LPA are the most prominent lysoglycerophospholipids and are considered to be inflammatory lipids involved in several immune-mediated diseases such as atherosclerosis and the autoimmune disease systemic lupus erythematosus (SLE) [ 32–35 ]. In our study, we found that LPC is significantly increased in psoriasis plasma and that PC shows the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that lysoglycerophospholipids, such as LPA and LPC, and glycerophospholipid metabolism, including PA, PC, and PI, were significantly altered in plasma from patients with psoriasis (Figs 4 and 6B and C). LPC and LPA are the most prominent lysoglycerophospholipids and are considered to be inflammatory lipids involved in several immune-mediated diseases such as atherosclerosis and the autoimmune disease systemic lupus erythematosus (SLE) [ 32–35 ]. In our study, we found that LPC is significantly increased in psoriasis plasma and that PC shows the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, total LPC levels were significantly lower in PbA-and Py-MV compared to uninfected mice and in PbA-compared to Py-MVs. Increased concentrations of circulating LPC is associated with inflammatory disorders 37 , and more recently has been found in increased amounts in platelet MV in myocardial infarction and atherosclerosis 38 and thereby are anti-inflammatory. In our study, 13 out of 16 DHA (22:6) containing lipids were found to be increased, while they were decreased in 2 out of 16 lipids in PbA-MV vs control-MV, suggesting an anti-inflammatory potential in MV circulating at the time of CM.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have revealed that the airway epithelium is a major source of LysoPC, as stimulation of cultured bronchial epithelial cells with growth factors led to increased release of bioactive forms of LysoPC [53]. Bansal and colleagues investigated the importance of LysoPC in a mouse model following exposure to cockroach extract and found that LysoPC promoted the maturation and recruitment of a subset of NKT cells to the airways, offering insights into the potential function of LysoPC in human asthma [54]. Another LysoPL byproduct from sPLA 2 activity, LysoPA, has both pro-and antiinflammatory roles in the airways, acting to regulate cytokines and chemokines in the airway epithelium [55][56][57].…”
Section: Functions Of Secreted Pla 2 S Relevant To Asthmamentioning
confidence: 99%